Turning Finance into Services for the Future : A Regional Synthesis of the Service Delivery Assessments for Water Supply and Sanitation in East Asia and the Pacific - World Bank Group (World Bank, Washington, DC, 2015)
From 2012 to 2014 water and sanitation service delivery assessments (SDA) have been carried out in seven selected countries in the East Asia and Pacific region under the guidance of the World Bank’s water and sanitation program and with valuable contributions of other development partners, such as United Nations Childrens Fund (UNICEF), WaterAid, and Asian Development Bank (ADB). Countries where SDA were carried out are Cambodia, Indonesia, Lao Peoples Democratic Republic (PDR), Papua New Guinea, Philippines, Timor-Leste, and Vietnam, while in Myanmar, a broad joint sector assessment took place by World Bank, UNICEF, ADB, and Japan International Cooperation Agency (JICA). SDA were implemented as a country-owned process led by key government agencies, and drew on the experience and methodology of similar assessments conducted in more than 40 countries (and states) in Africa, Latin America, and South Asia. It has three main components: a review of past water and sanitation access trends, a costing model to assess the adequacy of anticipated future investments, and a scorecard that allows diagnosis of bottlenecks along the service delivery pathways.